Natural Language Processing and Chinese Computing Second CCF Conference, NLPCC 2013, Chongqing, China, November 15-19, 2013, Proceedings - Zhou, Guodong; Li, Juanzi; Zhao, Dongyan; Feng, Yansong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Second CCF Conference on Natural Language Processing and Chinese Computing, NLPCC 2013, held in Chongqing, China, during November 2013. The 31 revised full papers presented together with three keynote talks and 13 short papers were carefully reviewed and selected from 203 submissions. The papers are organized in topical sections on fundamentals on language computing; applications on language computing; machine learning for NLP; machine translation and multi-lingual information access; NLP for social media and web mining, knowledge acquisition; NLP for search technology and ads; NLP fundamentals; NLP applications; NLP for social media.
Fundamentals on language computing -- Applications on language computing -- Machine learning for NLP -- Machine translation and multi-lingual information access -- NLP for social media and web mining, knowledge acquisition -- NLP for search technology and ads -- NLP fundamentals -- NLP applications -- NLP for social media.
Keywords: Computer science; Multimedia systems; Text processing (Computer science; Translators (Computer programs).; Computer Science; Language Translation and Linguistics; User Interfaces and Human Computer Interaction; Multimedia Information Systems; Document Preparation and Text Processing; Computer Applications